Sustainable Energy Policies and Equality: Is There a Nexus? Inferences From the Analysis of EU Statistical and Survey Data - Pellegrini-Masini, Giuseppe; Egner, Lars Even; Klöckner, Christian Andreas; Löfström, Erica (Frontiers in Sustainable Cities, 2021)
Energy equality (EE) is a novel concept, whose tentative definition was recently presented as follows: “Providing all individuals with equal opportunities of using energy services, energy technologies and consuming energy and embodied energy for satisfying personal needs and holding capabilities”. The complexity of the concept and its relationship with widely used concepts such as “needs”, “capabilities”, “energy justice”, “environmental justice” and “distributional justice” deserve to be analysed and discussed. Further, EE appears as a concept that is susceptible to inspire energy policies pursuing higher levels of distributional equity, thereby fostering capabilities and achieving CO2 emissions reductions. Distributional policies though, are known to be contentious and often raising debates on the opportunity of interfering with the free-market allocation of goods in capitalistic economies. Whether EE inspired policies might be considered as implementable also depends on their social acceptability; therefore holding on previous research findings pointing to the higher acceptability of equitable climate policies, we carry out a statistical analysis of EU statistical data regarding pro-environmental attitudes, pro-environmental behaviours and income inequality and of data from the H2020 ECHOES project, which consists of a large European survey of household energy consumption behaviours. We found that economic equality accounts for 41% of the variance explained at country level of our sustainable energy care index (SECI) accounting for sustainable energy attitudes. We conclude that the interplay between economic equality and sustainable energy attitudes deserve further attention and might warrant for a broader discussion about distributive policies within and beyond the energy sector.